PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP KINERJA REKSADANA CAMPURAN KONVENSIONAL (JEB17 : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine Fund Size, Turnover Ratio, inflation and interest rates on the performance of conventional mixed mutual funds during the COVID-19 pandemic. The method used in this study is a quantitative method. Sources of data used in this study is secondary data. The sampling technique used in this research is purposive sampling technique. The results of this study indicate that the results of the sig value of Fund Size and Turnover Ratio <0.05 while the sig value of inflation and interest rates> 0.05 so it can be concluded that the t-test results indicate that Fund Size and Turnover Ratio have a significant effect on mutual fund performance, while inflation and interest rates have no significant effect on mutual fund performance